Quality Characteristics, Antioxidant and Anticancer Potential of Stingless Bee Honey and Honeybee Honey from Similar Environmental Conditions - Yusof, Hayati; Zulpa, Ahmad Khusairy; Mohd Isa, Nur Suaidah; Tufail Ahmad, Fauziah; Kassim, Murni Nur Islamiah (IIUM Medical Journal Malaysia, 2021)
Introduction: The composition of the honey depends on the intrinsic and extrinsic factors, including place of origin, the floral types, the season and the storage conditions. This study compared the anticancer potential, quality, antioxidant and phytochemical between unprocessed stingless bee honey (SBH) and honeybee honey (HBH) from the same environmental factors including place of nest, floral type (Acacia), harvesting month (August) and storage conditions (<5°C). Materials and methods: To measure quality, 5-hydroxymethylfurfural (HMF) and diastase activity were determined, followed by total phenolic content (TPC) and total flavonoid content (TFC) for phytochemicals. Antioxidant activity was assessed via 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay. Cytotoxicity towards cervical cancer cell line (HeLa) was measured using a 2-(4,5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay (IC50). Results: The results indicated that HBH exhibited significantly higher diastase activity (2.17 ± 0.07 DN), TPC (338.95 ± 3.49 mg GAE/kg), DPPH scavenging activity EC50 (80.06 mg/ml) and MTT activity IC50 (64.80 mg/ml) towards HeLa as compared to SBH with absence of diastase activity, TPC (250.60 ± 3.98 mg GAE/kg), DPPH scavenging activity EC50 (165.80 mg/ml) and MTT activity IC50 (75.76 mg/ml). However, there were no significant differences in HMF and TFC between HBH and SBH. Conclusion: Therefore, the present study found that HBH demonstrates better antioxidant capacity, anticancer potential and phenolic content as compared to SBH.